Author Country: Longfellow, the Brontës, and Anglophone Homes and Haunts - Booth, Alison (Romanticism and Victorianism on the Net, 2007)
AbstractThis essay explores the nineteenth-century development of pilgrimage to authors’ houses and locales in light of British and American regionalism and literary reception. It focuses on the trope of “author country” in the celebrated careers and commemoration of Longfellow and the Brontës, and examines American “homes and haunts” books that represent ritual visits to these different authors. Various representations and sites, including portraits, statues, waterfalls, and houses, mark the indigenous qualities of national literature and international attractions.